Inflamed by the Flames?: The Impact of Terrorism and War on Immunity - Canetti, Daphna (J Trauma Stress, 2014)
The physiological impact of citizens’ prolonged exposure to violence and conflict is a crucial, yet underexplored issue within the political science and biology literature. We examined the impact of high levels of exposure to rocket and terrorist attacks on biological markers of immunity and inflammation in a sample of Israelis. A stratified random sample of individuals were drawn from a pool of subjects in Israel who have previously been interviewed regarding their stress exposure and psychological distress during a period of active rocket and terrorist attacks. These individuals were re-interviewed and blood samples were collected to assess antibodies to cytomegalovirus (CMV antibodies) and C-reactive protein (CRP). We concluded that PTSD was significantly related to CRP, controlling for BMI, depression, and exposure to terrorism. Depression scores did not significantly predict CRP (or CMV antibodies levels). In contrast to the established convention that psychological distress is the sole outcome of terrorism exposure, these findings reveal that individuals exposed to terrorism are at dual risk for PTSD/depression, and inflammation. This study has important ramifications for how policy makers and medical health professionals formulate public health policies and medically treat individuals living in conflict zones.